Projektowanie systemu rachunku kosztów dla ośrodków odpowiedzialności za koszty - Szydełko, Alfred (Designing the cost accounting system for cost centers, 2006)
This article shows the problems of management by means of cost centers. The efectiveness of this management increases when we design and implement cost accounting for cost responsibility centers. The appropriate cost accounting should be planning cost accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 383-390